EFFECT OF ZINC METAL STRESS ON SEED GERMINATION AND SEEDLING BEHAVIOUR OF VIGNA UNGUICULATA L. - AMEETA SHARMA; PARMILA (International Journal of Pharma and Bio Sciences, 2016)
The present study focuses on the germination response of different cowpea varieties to metal stress of Zinc and its relationship with the germination. The zinc stress was tested in different concentrations on three varieties of Vigna unguiculata viz. V1 (Pahuja), V2 (Rc 19) and V3 (Pusa Komal). Results all together showed that V1 variety was found to be resistant as compared to other two varieties and V2 was found to be relatively less sensitive than V3. Results suggested that all different concentration of metals damagingly influenced % germination and germination parameters like shoot, root, seedling length, fresh and dry weight of all three varieties up to certain extent.